Kenya's National Security Resilience: Way Forward (The Shivapuri Journal, 2024)
This article examines the expanding role of Kenya in addressing emerging security threats in a complex and unpredictable environment, where state response to security threats is being challenged by a wide range of actors and the salience for national security resilience is being awakened. Contemporary security threats to Kenya originate from other states, non-state actors, and disasters. They include; cyber-attacks, misinformation, transnational crimes, terrorism, pandemics, and radicalization. These threats are increasingly pressuring national security institutions and negatively impacting society. National Security Resilience therefore becomes an essential element in ensuring that the state is capable of responding, recovering, and adapting to security tragedies and disasters. The article posits that the whole government approach to security resilience can be further strengthened by expanding the resilience of citizens and communities. It implores that national security resilience not only requires government efforts but also individual and constituent communities' inputs. Contemporary Kenyan society is vastly networked, interdependent, at risk, and more vulnerable to the effects of emerging security threats and events. This makes it vital to have citizens and communities as the cornerstone of national security resilience efforts. It recommends that security efforts should focus on strengthening individual and community resilience.